Development of Carbon-Based Support Using Biochar from Guava Seeds for Lipase Immobilization - Lays C. de Almeida; Felipe A. de Jesus; Flávia M. S. Wiltshire; Roberta M. Santos; Alini T. Fricks; Lisiane dos S. Freitas; Matheus M. Pereira; Álvaro S. Lima; Cleide M. F. Soares (C, 2022)
Enzymes are promising tools for achieving an environmentally benign process. However, enzymes are required to be immobilized on economically competent supports to be reusable and maintain their activity. In this work, the aim was to evaluate the application of the biochar for immobilization of Burkholderia cepacia lipase (BCL) by physical adsorption (PA) and covalent binding (CB). Additionally, it was observed that regarding the biochemical properties, the optimal pH was 4.0 for the BCL immobilized by PA and pH 7.0 for the BCL free and immobilized by CB. Among the kinetic parameters, the maximal velocity (Vmax) for the free enzyme was 2500 µmol g−1·min−1, and for the PA- and CB-immobilized biocatalyst the values of Vmax were 2000 and 3333 µmol g−1·min−1, respectively. The Michaelis-Menten constant (Km) value for the free lipase was 665 mM and for the biocatalysts immobilized by PA and CB the Km values were 219 and 369 mM, respectively. Immobilized LBC exhibited superior thermal stability. The reusability tests showed that the LBC immobilized by PA preserved 50% of the initial activity after 16 cycles. Thus, biochar is a by-product of a renewable source; therefore, it is a promising alternative for lipase immobilization demonstrating its potential for use in a wide range of greener industrial processes.